STUDENTS’ COMPETENCE IN PREDICTING INFORMATION THROUGH PICTURE ON READING TEXT AT GRADE VIII STUDENTS OF JUNIOR HIGH SCHOOL - Putri Widya Ningsih and Rita Suswati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study is aimed to find out whether students pay more attention to picture, get information from picture and understanding the content of the text. It was conducted by using descriptive quantitative research. The source of the data was taken from the textbook entitled English in Focus published by Nur Ilmu, Yudhistira and students’ grade VIII of SMPN 3 Percut Sei Tuan. There are 9 classes of grade VIII which consists of 325 students, and VIII-1 was taken as the sample of this research. The data of this study were obtained from the students’ score of reading test. Based on the result of data analysis, it was found that the competence in predicting information through picture is very good. From 38 sample students, there were 21 students (55,3%) got very good score or can predict more than 5 details of information from the text, 15 students (39.5%) got good score or can predict less than 5 details of information from the text and only 2 students (5.2%) got bad score or predict less than 2 information. As well as their reading comprehension of the text with mean score 82.37 which is higher than the Minimal Completeness Criteria (KKM) of reading applied by SMPN 3 Percut Sei Tuan. It can be concluded that The result of this research is appropriate to the theory which claim that pictures are useful for getting students to predict what is coming next in a lesson and help the students comprehend the text easily.